Inositol supplementation in women with polycystic ovary syndrome undergoing intracytoplasmic sperm injection: a systematic review and meta-analysis of randomized controlled trials. Issue 5 (November 2017) - Mendoza, Nicolás; Pérez, Laura; Simoncini, Tommaso; Genazzani, Alessandro
Highlights: MYO supplementation is not enough to improve the oocyte or embryo quality and pregnancy rates in PCOS women undergoing ICSI. The role of DCI supplementation remains controversial or unknown. Abstract: Polycystic ovary syndrome (PCOS) is a complex and heterogeneous disease that involves menstrual dysfunction and reproductive difficulty, as well as metabolic problems. The aim of this study was to assess the effectiveness of myo-inositol (MYO) and d-chiro-inositol (DCI) on improving oocyte or embryo quality and pregnancy rates for women with PCOS undergoing intracytoplasmic sperm injection (ICSI). We searched the Web of Knowledge, MEDLINE, EMBASE, Pubmed, Scopus and Cochrane databases for all articles published in any language up to March 2017. The selection criteria were as follows: (population) patients with PCOS; (intervention) treatment with inositol (MYO, DCI, or both, with any dose and any duration) in conjunction with an ovulation-inducing agent versus the ovulation-inducing agent alone; (outcome) oocyte and embryo quality; (study design) randomized controlled trials. Of 76 identified studies, eight RCTs were included for analysis comprising 1019 women with PCOS. MYO supplementation was insufficient to improve oocyte quality (OR 2.2051; 95% CI 0.8260 to 5.8868), embryo quality (OR 1.6231, 95% CI 0.3926 to 6.7097), or pregnancy rate (OR 1.2832, 95% CI 0.8692 to 1.8944). Future studies of appropriate dose, size and duration of DCI are vital to clarify its the role in the management of PCOS.